Talent Management and its Effect on Employee Engagement: A Field Study on Islamic Banks Operating in the Capital Municipality of Sana'a, Yemen - Amaal Motaher Abdo Khosrof; Murad Mohammed Al-Nashmi (University of Science and Technology, Sana’a, Yemen, 2024)
This study aimed to identify the impact of talent management (TM) on employee engagement (EE) in Islamic banks operating in the Capital Municipality of Sana’a, Yemen. The study adopted the descriptive analytical method and developed a questionnaire as the study instrument. The study population consisted of 1024 workers in Islamic banks in Sana’a, and the sample size was 280 individuals selected by using disproportionate stratified random sampling. Out of 280 distributed questionnaires, 276 were valid for statistical analysis via SPSS (V. 25). The results revealed that TM is practiced at a high level in the surveyed banks through all its dimensions. EE is also practiced at a high level in the surveyed banks, with vigor and dedication being higher than absorption. Results also indicated that TM has a significant positive impact on EE in the surveyed Islamic banks, except for talent retention, which has no significant effect. Based on these findings, it was recommended that Islamic banks should maintain and enhance the high level of practice of EE among their employees, focusing on the factors that foster EE. Furthermore, the aforementioned banks should pay more attention to TM practices and provide the necessary means to attract, develop, and retain talented workers.